Elamipretide protects H9c2 Rat Cardiomyoblasts against Doxorubicin-Induced Disruption of Mitochondrial Quality Control by Restoration of Fusion and Fission Balance - Mahmoud, Marwa; Arif, Inaam S.; AL-Ezzi, Muthanna I. (Iraqi Journal of Pharmaceutical Sciences, 2024)
Doxorubicin (DOX) has been used to treat malignant diseases for over 40 years. The main constraint to its clinical application is dose-dependent cardiotoxicity which is regarded as a major matter of concern that limits its medical usefulness. Mitochondrial dysfunction is considered the chief contributor to DOX-induced cardiotoxicity and it involves disruption of mitochondrial quality control, mainly impaired fusion, and enhanced fission processes. Compounds that specifically target the mitochondria and restore fusion and fission balance are considered a promising tool to protect or treat cardiomyopathy and heart failure and thus could be investigated as a novel strategy to alleviate DOX-induced cardiac toxicity, one of which is elamipretide (ELAM). In this study, MTT assay revealed that DOX induces a significant reduction in H9c2 cell viability which is both time and dose-dependent whereas ELAM has no significant effect on the viability of the relevant cells at most of the concentrations used. Additionally, western blot analysis showed a significant reduction in the expression of fusion protein MFN2 in the DOX-treated group compared to the control (p***< 0.001) whereas the fission protein DRP1 was significantly upregulated in DOX-treated cells compared to the control (p**< 0.01) and normalization of both proteins was achieved when 10 µM ELAM introduced 48-hour prior to DOX therapy. In conclusion, ELAM could exert an interesting cardioprotective role against DOX-induced cardiotoxicity by restoration of mitochondrial fusion and fission balance.